Towards synergy of VLBI and GNSS geodetic techniques in geologically dynamic New Zealand - Takiguchi, H; Gulyaev, S; Natusch, T; Weston, S; Woodburn, L (Asia Oceania Geosciences Society (AOGS), 2011)
Though the New Zealand Geodetic Datum 2000 (NZGD2000) is based on and closely matches the International Terrestrial Reference System (ITRS) through the International Terrestrial Reference Frame (ITRF), it is not a dynamic system. NZGD2000 is defined by its relationship to a dynamic global reference frame at a specified epoch (2000.0) and does not include coordinate changes that occur in geologically dynamic New Zealand as a result of earthquakes and tectonic motions. Monitoring of changes between the datum as a whole and the global reference system (ITRF) is essential. While GNSS stations network allows building a relative local velocity model, VLBI is able to directly link this (local) model to the ITRF. Development of New Zealand VLBI service for geodesy is, therefore, one of the central tasks in sustaining the New Zealand Geodetic Datum 2000 and maintaining its link to the ITRF. VLBI is also capable to contribute to solution of the problem of vertical datum development in New Zealand. A 12-m geodetic radio telescope has been built in New Zealand near township of Warkworth, 60 km north of Auckland. Recently, it became a network station of the International VLBI Service for Geodesy and Astrometry (IVS) and started regular observations in the framework of IVS geodetic observational programs. The radio telescope is collocated with a GNSS station operated by Land Information New Zealand (LINZ). The inter-technique (VLBI and GNSS) solution is capable of increasing reliability of the national geodetic infrastructure. Here we outline a VLBI program focusing on the synergy with GNSS geodetic network in New Zealand. Comparison of the first coordinate measurements conducted with GNSS and VLBI techniques are provided, and discrepancy between these results is discussed.
Keywords: Space geodesy; Geodetic datum; Reference frame; VLBI; GNSS; IVS